A double-layer Huygens’ metasurface with complete phase coverage and its dual-polarized meta-lens antenna application - Zhou, Jianhe; Xiong, Yingxiang; Peng, Qichang; Bin, Zhiyan; Xue, Chunhua (Frontiers in Physics, 2023)
A novel double-layer Huygens’ unit with dual-polarized response and complete phase coverage has been proposed for highly efficient meta-lens antenna application. The designed unit is a symmetric structure in which the double-layer metallic patterns not only act as the electric dipoles but also induce the magnetic dipoles. The balance between the initial electric dipole and the induced magnetic dipole makes the impedance of the metasurface match with that of free space, thus allowing efficient transmission of electromagnetic waves. Moreover, full transmission phase shift and near-unit transmission amplitude can be achieved simultaneously by change the structural parameters of the unit. Utilizing such electromagnetic properties, a dual-polarized meta-lens consisting of 35 × 35 units with size of 161 × 161 mm2 is designed, fabricated and measured. The results exhibit its good radiation performance. The maximum gain at a frequency of 28 GHz reaches 30.8 dBi, with an aperture efficiency of 42.3%. The 3-dB gain bandwidth reaches 12.5%, covering the frequency range of 26.7–30.2 GHz. The simple structure of the designed dual-polarized metasurface, high gain and high antenna efficiency make it an important antenna engineering role.